2010
DOI: 10.1002/jso.21802
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of USP22 is associated with liver metastasis and poor prognosis of colorectal cancer

Abstract: USP22 might be an independent predictive factor for CRC prognosis and aberrant expression of USP22 may play an essential role in colorectal carcinogenesis and liver metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
90
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(98 citation statements)
references
References 25 publications
8
90
0
Order By: Relevance
“…Given that USP22 overexpression is correlated with several aggressive cancers (3,16,22), we examined ATXN7L3B protein levels in normal mammary, estrogen receptor-positive (ER ϩ ), and HER2-positive (HER2 ϩ ) breast cancer cell lines (Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that USP22 overexpression is correlated with several aggressive cancers (3,16,22), we examined ATXN7L3B protein levels in normal mammary, estrogen receptor-positive (ER ϩ ), and HER2-positive (HER2 ϩ ) breast cancer cell lines (Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Our data provide new insights into ATXN7L3B functions in regulating USP22 activity and localization. Since USP22 overexpression is observed in several highly aggressive cancers (15,16), we also asked whether ATXN7L3B has functions in breast cancer. We found that ATXN7L3B is highly expressed in estrogen receptor-positive (ER ϩ ) breast cancer cell lines.…”
mentioning
confidence: 99%
“…A large body of research has linked this enzyme to tumour progression and oncogenic activity, and USP22 is currently under investigation as a therapeutic target for cancer. Elevated expression has been shown to act as a key indicator of poor prognosis in a variety of different cancers including invasive breast cancer (Zhang et al 2011a), colorectal carcinoma (Liu et al 2011), oesophageal cancer , papillary thyroid carcinoma (Wang et al 2013b), gastric cancer , oral squamous cell carcinoma (Piao et al 2012), salivary duct carcinoma (Piao et al 2013), non-small cell lung carcinoma (Ning et al 2012) and cervical cancer (Yang et al 2014). In addition, inhibition of USP22 has been demonstrated to induce cell cycle arrest and inhibit proliferation in hepatocellular carcinoma (HCC; Ling et al 2012) and bladder cancer (Lv et al 2011).…”
Section: 'Erasing' H2bub1: Dubsmentioning
confidence: 99%
“…Beyond its SAGA-related functions, the study of USP22 has been relatively limited, although several reports have uncovered correlative links to human pathology. For instance, USP22 has been shown to be part of an 11-gene death-from-cancer signature that is predictive of treatment failure (48,49), and its increased expression is associated with a poor prognosis in a variety of cancers (50,51).…”
mentioning
confidence: 99%